2004
DOI: 10.1257/.42.1.116
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Studies of Financial Innovation: Lots of Talk, Little Action?

Abstract: This paper reviews the extant empirical studies of financial innovation. Adopting broad criteria, we found just two-dozen studies (24), over half of which (14) had been conducted since 2000. Since some financial innovations are examined by more than one study, only 14 distinct phenomena have been covered. Especially striking is the fact that only two studies are directed at the hypotheses advanced in many broad descriptive articles concerning the environmental conditions (e.g., regulation, taxes, unstable macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
162
0
24

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(186 citation statements)
references
References 6 publications
0
162
0
24
Order By: Relevance
“…As a theoretical matter, there is no presumption that more financial innovation contributes to higher social welfare. Mathematical models created to demonstrate how financial innovation operates in an economy have shown that, in principle, they can either increase or decrease social welfare (Elul, 1995;Frame and White, 2004).…”
Section: The Social Efficiency Of Financial Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a theoretical matter, there is no presumption that more financial innovation contributes to higher social welfare. Mathematical models created to demonstrate how financial innovation operates in an economy have shown that, in principle, they can either increase or decrease social welfare (Elul, 1995;Frame and White, 2004).…”
Section: The Social Efficiency Of Financial Innovationmentioning
confidence: 99%
“…But what about social impacts? Frame and White (2004) published a comprehensive survey of the determinants and effects of financial innovation. As their paper shows, there has been relatively little study of financial innovation.…”
Section: The Social Efficiency Of Financial Innovationmentioning
confidence: 99%
“…"Everybody talks about financial innovation, but (almost) nobody empirically tests hypotheses about it." Frame and White (2004) "I wish somebody would give me some shred of evidence linking financial innovation with a benefit to the economy." 1 Paul Volcker, former Chairman of the Federal Reserve…”
Section: Introductionmentioning
confidence: 99%
“…2 In early 2010, the Economist organized a 10-day online debate between Ross Levine and Joseph E. Stiglitz on the role and benefits of financial innovation: http://www.economist.com/debate/overview/166. 3 See discussion in White (2004 and) who conduct a thorough survey of the empirical literature on financial innovation. For theoretical literature related to financial innovation, Duffie and Rahi (1995) introduce a special issue of Journal of Economic Theory.…”
Section: Introductionmentioning
confidence: 99%
“…Although product innovation has played a significant role in transforming many industries, Frame and White () note that there are few empirical studies of the impact of innovation in the financial services industries. In particular, little academic attention has been focused on the role of innovation in the insurance industry .…”
Section: Insurance Innovation and Adverse Selectionmentioning
confidence: 99%